Paisaje Cultural Cacaotero: “Reconocimiento de la arquitectura vernácula de las fincas cacaoteras en el municipio de Campoalegre-Huila” (2021)
The following degree work aims to recognize the historical and heritage importance of the cocoa farms in the north of Huila, putting architecture as the backbone of the social, cultural and economic development of this region of the country. Analyzing the architectural tradition, construction methods, typology, image, materiality and functioning of these architectural spaces that are the axis of a tradition of many years, this work rescues for the next generations a historical legacy that for lack of interest tends to disappear. In the north of the Department of Huila the inhabitants of the cocoa farms do not have an adequate recognition of their important infrastructures that are being forgotten, and its exaltation works on the collection of important information about its construction systems, forms, techniques, etc. The present book is based solution of the absence of recognition of the cocoa farms of the municipality of Campoalegre Huila being able to recover and exalt a legacy for this important municipality of the department.